Cases of Zika virus infection in Turkey: newly married couple returning from Cuba - Alper, Sezen; Yıldırım, M.; Kültür, MN.; Pehlivanoğlu, F.; Menemenlioğlu, D. (My University, 2018)
Zika virus is a Flavivirus in the family Flaviviridae, and transmitted to humans by Aedes species mosquitoes. Zika virus infection is asymptomatic in 80% of cases and has a mild course when symptoms occur. These symptoms include headache, myalgia, mild fever, maculopapular rash and conjunctivitis. Zika virus has been associated with serious neurological complications such as Guillain-Barre syndrome in adults and microcephaly development in neonates. It has recently become a global public health problem as a result of increasing cases. As it is known that the vector of this disease is present in our country; entry of Zika virus infection in our country has a great importance. In this report the clinical and laboratory findings of two cases of Zika virus infection imported to Turkey by a couple returning from Cuba in October 2017 were presented. Newly married couple, both 29 years old, without a known chronic disease history, went on honeymoon to Cuba between 17-29 September and they visited Havana and Varadero. They reported that they were bitten repeatedly by the mosquitoes and did not use insect repellents during this time. Four days after returning to Turkey, they had headaches, back pain and myalgia followed by rash and joint pain. They reported having their symptoms started in the same day in a few hours difference. The symptoms for both patients disappeared in 10 days. Serum samples from the patients were sent to the Public Health General Directorate National Arboviruses and Viral Zoonoses Laboratory to be tested for Dengue, Chikungunya and Zika viruses. Nucleic acid testing yielded negative results. The Arbovirus Indirect Immunofluorescence test were positive both for IgM and IgG for Zika virus. No cross reactivity with Dengue virus was detected. Chikungunya antibodies were found as negative. At two months of the diagnosis, urine and semen samples of the male patient were tested by real-time reverse transcriptase polymerase chain reaction (rRT-PCR). The result was negative for urine but positive for semen sample. This report is important to present the first cases of Zika virus infection published in Turkey. Zika virus infection should be suspected in patients with fever, headache, rash, myalgia and joint pain returning from an endemic areas. All travelers, especially pregnant women, have to take precautions for mosquitos during the trip.